A Review on Silver Nanoparticles Based Biomaterials for Bone Tissue Engineering and Medical Applications - Sari, Nasmi Herlina; Rivlan, Muhammad Zaidan Fadhlurrohman; Suteja, Suteja; Kadriyan, Hamsu; Thiagamani, Sentil Muthu Kumar (Universitas Gadjah Mada, 2024)
Silver nanoparticles (AgNPs) are being studied extensively as nanostructures for novel and enhanced biomedical applications. Nanoparticles in bone grafts have been shown to speed up fracture healing by providing a finer structure for bone tissue engineering. They are known to have excellent antimicrobial properties due to their high surface-to-volume ratio and small particle size, without affecting the material's mechanical properties. AgNPs' distinct property makes them the preferred filler in a wide range of biomaterials, where they play an important role in enhancing properties. AgNP-containing biomaterials can be easily tailored to meet specific requirements in the development of bone tissue. Adjusting size, shape, composition, and surface charge can enhance their effectiveness in interacting with bone cells, promoting cell attachment, and delivering growth factors. Using AgNP-based biomaterials can help prevent or reduce the formation of biofilms. The utilization of these materials in bone tissue engineering has demonstrated potential in treating musculoskeletal conditions and bone traumas. They are versatile for various applications such as bone implants, scaffolds, wound dressings, and antibiotic delivery systems. This review will cover several special topics, including silver-based biomaterials, toxic properties, morphology and mechanical properties of silver-based biomaterials, and applications of silver-based biomaterials in medical applications.